Higher experience of caries and lower income trajectory influence the quality of restorations: A multilevel analysis in a birth cohort. (January 2018) - Collares, Kauê; Opdam, Niek J.; Peres, Karen G.; Peres, Marco A.; Horta, Bernardo L.; Demarco, Flávio F.; Correa, Marcos B.
Abstract: Objectives: This study aimed to evaluate the quality of posterior restorations (amalgam or composite) placed in adults from a birth cohort and its association with clinical and socioeconomic determinants experienced during their life course. Methods: A representative sample (n = 539) of all 5914 births occurring in Pelotas (Brazil) in 1982 was prospectively investigated. Quality of posterior restorations (satisfactory or unsatisfactory) was assessed at 31 yrs-old, using modified USPHS criteria. Trained and calibrated dentists performed clinical examination. Explanatory variables included demographic and socioeconomic, oral health and dental service utilization patterns during the life course. Tooth related variables (type of tooth, material, size of cavity) were also analyzed. Untreated caries and socioeconomic status were assessed by group-based trajectories analyses. Multilevel Regression models were used to determine factors associated with restoration outcomes. Results: In total 2123 restorations (53% composite) were evaluated of which 107 (5%) were assessed as failed. The main reasons for failure were tooth/restoration fracture (50.5%) and secondary caries (30.7%). Failures in posterior restorations showed a significant association with socioeconomic aspects (lower tertile of income at age 30 – prevalence ratio (PR) 2.21 [95% CI 1.19–4.09]), clinical variables (trajectory of higher untreated caries – PR 2.11 [95% CI 1.23–3.61]) and also with tooth-related factors (Restorations involving three or more surfaces – PR 5.51 [95% CI 3.30–9.19]) after adjustment for each other. Conclusions: These findings suggest that, although tooth-related variables have an important role in restoration longevity, patient-related factors, such as socioeconomic variables and untreated caries are also associated with failure and should be taken into account when evaluating longevity of posterior restorations. Clinical significance: This was the first study assessing long-term trajectory of untreated caries, showing an association between higher experience of caries during the life-course and unsatisfactory restorations. The findings suggest that individual related factors should be considered when planning treatment and in future research evaluating the longevity of dental restorations.